Cushion Mechanism of Goat Hoof Bulb Tissues - Weijun Tian; Hai Liu; Qi Zhang; Bo Su; Wei Xu; Qian Cong (Applied Bionics and Biomechanics)
The hoof bulb sections of white goats were observed via scanning electron microscopy and stereomicroscopy in order to explore the cushion mechanism in the bulb tissue microstructures of hoofed animals. The hoof bulbs consisted of multilayer tissues, including an epidermal layer, a dermal layer, and subcutaneous tissues from outside to inside. A bionic model based on hoof bulb tissue composite structures was built with a normal model as the control. The microcosmic mechanics of the bulb tissues was analyzed via the finite element method. Simulations showed that when the bionic model was impacted by the top plates at the speed of 1-10 m/s, stress was concentrated in the epidermal layer and uniformly distributed in the dermal layer and dermal papillae, which effectively reduced the impact onto the ground. The cornified epidermal layer can resist the instant impact onto the ground, while the dermal papillae embedded in the dermal layer can store, release, and dissipate the impulsive energy, and the three parts synergically act in the cushion.